Peran Pesantren Dalam Pendidikan Wanita Islam: Studi Kasus Pondok Pesantren Puteri Ummul Mukminin - Nur, Indria (Al-Riwayah : Jurnal Kependidikan, 2016)
Islamic Boarding School (Pesantren) is considered by the social society as the agent of moral force that has given major contribution to the Islamic educational institutions in achieving what so called perfect human being, by upholding morals and morality in the society, particularly for women in Islam. Therefore, in order to create a modern and intelligent generation, Islamic Boarding Schools advances women’s Islamic education. How and in what way Ummul Mu’minin takes this role, has inspired researchers to study it. This paper is a case study that shows that the existence of girls Islamic Boarding School (Pesantren) of Ummul Mukminin coordinated by ‘Aisyiyah in South Sulawesi region is one those Islamic educational institution that is able to accelerate Muslim women’s educational progress. Therefore, this Pesantren is expected to continue enhancing its contribution in the community development, especially Muslim women, as well as the extensive development of Islamic thought that can answer the challenges of civilization in globalization era, even as a pioneer for other Islamic educational institutions in shaping modern, intelligent Islamic women generations.